2002
DOI: 10.1002/ajh.10244
|View full text |Cite
|
Sign up to set email alerts
|

Novel β‐thalassemia trait (IVS I‐1 G→C) in a Japanese family

Abstract: A rare ␤-thalassemia mutation at the splicing junction [namely, G→C in intervening sequence (IVS) I-1] was found in a Japanese family. The proband and his mother were heterozygous for the mutation. Analysis of mRNA extracted from the reticulocyte-rich fraction obtained from the proband's mother revealed that the mutant ␤-globin gene did not produce any detectable, stable mRNA including exon 1 and exon 2, since the polymorphism in exon 1 on her mutant gene was not detected in the RT-PCR products. Am.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…IVS I-5 G/C is the most common beta thalassaemia mutation in these areas and can lead to severe β+ thalassaemia. However the IVS II-666 T/C is a neutral polymorphism previously found in Saudi Arabia and in a Japanese family [5,6]. Lin in a larger study, (where microcytosis was defined as MCV<82 FL), in China showed a high prevalence of thalassaemia carriers (both alpha and beta, with heterozygote frequency ranging from 2.63% to 9.49% in different parts of one province [7].…”
Section: Resultsmentioning
confidence: 99%
“…IVS I-5 G/C is the most common beta thalassaemia mutation in these areas and can lead to severe β+ thalassaemia. However the IVS II-666 T/C is a neutral polymorphism previously found in Saudi Arabia and in a Japanese family [5,6]. Lin in a larger study, (where microcytosis was defined as MCV<82 FL), in China showed a high prevalence of thalassaemia carriers (both alpha and beta, with heterozygote frequency ranging from 2.63% to 9.49% in different parts of one province [7].…”
Section: Resultsmentioning
confidence: 99%
“…Some cases of mRNA-de¢cient b-thalassaemia involve large deletions 7 or rearrangements of the b-globin genes; however, most cases are reported to be caused by other genetic mutations that a¡ect transcription, 1 RNA processing, 2 RNA transport (nucleus to cytoplasm), 3 mRNA stability in the cytoplasm, 4 nonsense-mediated mRNA decay, 5 or a combination of these factors. In this study to examine the cause of the drastically reduced mutant mRNA level in the reticulocytes from a patient with a G4C splicing junction mutation in IVS1--1of the b-globin gene, 6 we analysed the mRNA encoded by the cloned mutant gene in COS-1 cells. Our transient expression system using COS-1 cells indicated that the mutant gene containing IVS1--1C was transcribed at a similar level to the normal gene (analysed by RT-PCR), and this transcription was followed by the splicing and processing of the mutant RNA.…”
Section: Resultsmentioning
confidence: 99%
“…However, we did not observe these minor bands of mRNAs in vivo in the reticulocytes from the normal control or the proband. 6 The nucleotide sequences of these 5 0 and 3 0 'cryptic' splice sites are listed in Figure 2, and compared with the sequences of the normal 5 0 splice site of IVS1 or the 3 0 splice site in the 3 0 -£anking region as well as the consensus sequence of the 5 0 or 3 0 splice site.We think that unexpected splicing products from the normal (W2 and W3) and mutant (T3 and T4) b-globin gene might be produced by excess transcription occurring in the COS-1 cell expression system (gene dosage e¡ect caused by the combination of the T-antigen in the cells and the SV40-ori on the vector) and the highly e⁄cient promoter derived from cytomegalovirus in the pcDNAI. Furthermore, the excess expression may lead to aberrant RNA processing, including aberrant transportation, degradation of RNA and so on.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations